Risk in Chiang Mai tourism supply chain - K. Y. Tippayawong (2018)
© Research India Publications. The study focuses on assessing risk in tourism supply chain in Chiang Mai. Risk factors are identified based on literature review. In the study, 10 internal risks and 31 external risks are used. The result of the study yields from 255 returned questionnaires. For Chiang Mai tourism supply chain, Political Uncertainty, Economic Recession, Increased Domestic Competition, Competitor Cost Advantage, Decrease in Tourist Disposable Income, Rising of Fuel Cost, Image of Destination, Tourism Preference Change, Increased International Competition and Competitor Variety of Product are ranked as top 10 risks. However, concern varies between members as their driving value.